Adenosine Methylation in Arabidopsis mRNA is Associated with the 3′ End and Reduced Levels Cause Developmental Defects - Bodi, Zsuzsanna; Zhong, Silin; Mehra, Surbhi; Song, Jie; Li, Hongying; Graham, Neil; May, Sean; Fray, Rupert G. (Frontiers in Plant Science, 2012)
We previously showed that the N6-methyladenosine (m6A) mRNA methylase is essential during Arabidopsis thaliana embryonic development. We also demonstrated that this modification is present at varying levels in all mature tissues. However, the requirement for the m6A in the mature plant was not tested. Here we show that a 95% reduction in m6A levels during later growth stages gives rise to plants with altered growth patterns and reduced apical dominance. The flowers of these plants commonly show defects in their floral organ number, size and identity. The global analysis of gene expression from reduced m6A plants show that a significant number of down regulated genes are involved in transport, or targeted transport, and most of the upregulated genes are involved in stress and stimulus response processes. An analysis of m6A distribution in fragmented mRNA suggests that the m6A is predominantly positioned towards the 3’ end of transcripts in a region 100-150 bp before the poly(A) tail. In addition to the analysis of the phenotypic changes in the low methylation Arabidopsis plants we will review the latest advances in the field of mRNA internal methylation